Clonal Changes in the Pneumococcal Population Carried by Portuguese Children during Six Years of Private Use of the 13-Valent Pneumococcal Conjugate Vaccine - Candeias, Catarina (2023)
Funding Information: Editor Max Maurin, UJF-Grenoble 1, CHU Grenoble Copyright © 2023 Candeias et al. This is an open-access article distributed under the terms of the Creative Commons Attribution 4.0 International license. Address correspondence to Raquel Sá-Leão, rsaleao@itqb.unl.pt. The authors declare a conflict of interest. This work was partially supported by Investigator Initiated Grants WI182109 and WI230921 from Pfizer Portugal (to R.S.-L.), LISBOA-01-0145-FEDER (Microbiologia Molecular, Estrutural e Celular, funded by FEDER through COMPETE2020 - Programa Operacional Competitividade e Internacionalização), and Fundação para a Ciência e a Tecnologia (C.C., S.F., S.H., were supported by PhD fellowships PD/BD/148434/2019, PD/BD/105732/2014, and PD/BD/128365/2017, respectively). Received 27 July 2022 Accepted 25 February 2023 Published 22 March 2023 Funding Information: This work was partially supported by Investigator Initiated Grants WI182109 and WI230921 from Pfizer Portugal (to R.S.-L.), LISBOA-01-0145-FEDER (Microbiologia Molecular, Estrutural e Celular, funded by FEDER through COMPETE2020—Programa Operacional Competitividade e Internacionalização), and Fundação para a Ciência e a Tecnologia (C.C., S.F., and S.H. were supported by PhD fellowships PD/BD/148434/ 2019, PD/BD/105732/2014, and PD/BD/128365/2017, respectively). Publisher Copyright: Copyright © 2023 Candeias et al.